دراسة قابلية الخلايا اللمفاوية التائية على التحول و الأنقسام في المرضى المصابين بألتهاب المفاصل الرثوي و داء الذئب الأحمراري - رحمن سناء; رحمن هناء; صادق غنيمة (Al-Nahrain Journal of Science, 2018)
T-Lymphocytes transformation is considered one of the cellular immune response aspects for that we studied this process in patients with Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE) by using phytohaemagglutinin (PHA) as mitogen, the results was showed asignificant reduction (P<0.001) in the mean of stimulation and division of T-Lymphocytes in the patients with RA compared with healthy control group, while there was no significant differences compared with patients with osteoarthritis (OA). Also the results showed that is the lymphocytes transformation of SLE patients were more decreased compared with that of control groups (P<0.001). The results showed that disease activity (active or non-active) had an effect on T-lymphocytes transformation by using PHA, the mean of division in patients with non-active disease was higher than active disease. The study examined the relationship between long term treatment (Methotrexate, Chloroquine) and effect of this on cellular immune response, we found that the prolonged period of treatment cause decrease in lymphocytes transformation for RA patients, on the other hand the study showed that patients with SLE have no significant relationship between long term treatment on T-lymphocytes transformation.